Integrating Computational Thinking in Rural Middle School Art Classes in Eastern North Carolina - Reardon, R. Martin (Theory & Practice in Rural Education, 2022)
With funding from a National Science Foundation (NSF) grant, an innovative endeavor to integrate computational thinking into the teaching of both music and visual arts in three rural school districts in North Carolina was launched in early December 2018. Over the next five years—a time span that encompassed a major hurricane which devastated the area and the COVID-19 pandemic—the partners in a research practitioner partnership collaborated to create and refine curricular activity system projects in both subject areas. This paper is focused on the visual arts component of the grant activities. After discussing the genesis of the project, I situate it as contributing to the cultural capital of the middle school student participants and situate it theoretically in cognitive flexibility theory. I then discuss the operational definition of computational thinking that underpinned the design of the elements of the curricular activity system which were then refined and adapted to the rural contexts in collaboration with the teachers. I provide an overview of the curricular activities (a professional development website was created by grant colleagues at University 2) and discuss students’ perspectives on the concepts and approaches of computational thinking. I close with reflections on the importance of the project.